DISCRETE CHOISE ANALYSIS AS A TOOL IN MARKETING RESEARCH AND ITS IMPLEMENTATION IN THE SAS SYSTEM - Nusar Hajarisman; Mardha Tri Meilani; Hardiana Prasasti (STATISTIKA: Forum Teori dan Aplikasi Statistika, 2003)
Discrete choice modeling, a somewhat newer technique in preference structure modeling of marketing research thanconjoint analysis. This model differs in that consumers are asked to view a series of competing products and select one. In thisregard, it is based on a move realistic task that consumers perform every day: the task of choosing a product from among a groupof competitor. Discrete choice models can be used to perform powerful and complex simulation of marketplace for an entireproduct or service category. The impact of price change and product enchangments on brand shares can be simulated before theyare implemented, as can the effects of potential competitive response to these action. Futher, discrete choice models are muchbetter than conjoint analysis at duplicating the interactions between different characteristics of a product or service. We usePHREG procedure in the SAS system to estimate the dicrete choice model.